Hydrocarbon potential, maturity and depositional environment of the source rocks in the Southwestern part of the Naga Schuppen Belt, India. (18th August 2021) - Gogoi, Mousumi; Kumar, T. Satish; Mathur, Neeraj; Walling, Temsulemba; Phukan, Sarat
The organic matters in the Oligocene Laisong and Jenam Formations, exposed along the Dimapur-Kohima road section in the Naga Schuppen Belt, Nagaland, have been characterised by Rock-Eval pyrolysis, biomarker analysis and organic petrographical analysis. The organic matters are mostly mixed type II & III, and type III kerogens in the Laisong Formation and, type III and IV kerogens in the Jenam Formation deposited mostly in an oxic deltaic-terrigenous environment. The organic matters of both formations generally show poor hydrocarbon generative potential. Maturity parameters are indicative of the presence of immature to early mature organic matters in the Laisong Formation and early to mid-mature organic matters in the Jenam Formation. This is quite unusual as the Jenam Formation overlies the Laisong Formation. This mismatch was possibly caused by many episodes of rapid differential heating to high temperature followed by cooling related to active tectonics of the Naga Schuppen Belt. [Received: August 14, 2019; Accepted: August 7, 2020]